Analiza stanja in izzivi na področju komasacij kmetijskih zemljišč v Sloveniji - Lisec, Anka (Geodetski vestnik, 2013)
This article is about the activities of agriculturalland consolidation in Slovenia and some criticalpoints regarding their implementation. The study hasfocused on administrative land consolidations, whichare implemented in accordance with the legislationregarding agricultural land management. In theresearch, the role of the individual land consolidatorconsolidations actor in land consolidation procedureswas studied. For this purpose, an inquiry into the landconsolidation participants, administrative units andmunicipalities was conducted. It has been observedthat in Slovenia the support of public institutions inthe field of land consolidation is extremely weak. Theexceptions are the areas with significant experiencein this field, where land owners and consolidationparticipants are generally extremely satisfied withthe results. Nowadays, land consolidation may be apart of a development project. The praxis in Sloveniastill follows the traditional approaches, partly due tothe weak public institutional support in comparisonto foreign experiences. Land consolidation should beconsidered to be an instrument of national interest,due to benefits such as improvement of conditionsfor agricultural and rural development, landscapearrangements, supporting food self-security, not tomention other benefits such as new cadastral surveyingand qualitative spatial data in the framework of landand spatial information systems.
Keywords: agrarian operations; agrarne operacije; agricultural land; forest; gozd; kmetijsko zemljišče; komasacija; land; land consolidation; land management; razvoj podeželja; rural development; Slovenia; Slovenija; upravljanje zemljišč; zemljišče